2020
DOI: 10.3390/nano10050912
|View full text |Cite
|
Sign up to set email alerts
|

InGaN Nanorods Decorated with Au Nanoparticles for Enhanced Water Splitting Based on Surface Plasmon Resonance Effects

Abstract: Photoelectrochemical (PEC) water splitting has great application potential in converting solar energy into hydrogen energy. However, what stands in the way of the practical application of this technology is the low conversion efficiency, which can be promoted by optimizing the material structure and device design for surface functionalization. In this work, we deposited gold nanoparticles (Au NPs) with different loading densities on the surface of InGaN nanorod (NR) arrays through a chemical solvent route to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In recent years, transition metal nitrides have received widespread attention as intermetallic compounds for photocatalytic applications owing to their good electrical conductivity and narrow band gap [50] . In Liu's work, [51] Au nanoparticles were deposited onto the surface of InGaN nanorods (NRs) to significantly improve the photocatalytic efficiency. The SPR effect induced by Au nanoparticles promoted the separation of electron‐hole pairs while the nanorod structure of InGaN had a larger bulk surface area to capture more light.…”
Section: Emerging Hybrid Systems Containing Metalsmentioning
confidence: 99%
“…In recent years, transition metal nitrides have received widespread attention as intermetallic compounds for photocatalytic applications owing to their good electrical conductivity and narrow band gap [50] . In Liu's work, [51] Au nanoparticles were deposited onto the surface of InGaN nanorods (NRs) to significantly improve the photocatalytic efficiency. The SPR effect induced by Au nanoparticles promoted the separation of electron‐hole pairs while the nanorod structure of InGaN had a larger bulk surface area to capture more light.…”
Section: Emerging Hybrid Systems Containing Metalsmentioning
confidence: 99%
“…However, the current density of a GaN-NW photoanode is theoretically limited to less than 10 mA/cm 2 because of the large interfacial charge-transfer resistance and fast recombination of photoinduced charge carriers largely due to upward bending of the energy-band at the GaN surface . Attempts to overcome the influence of the surface-trap states to improve the PEC-WS performance led to the passivation of the NW surface using noble metals, such as Au and IrO 2 . , For example, Liu et al reported an InGaN-nanorod photoanode decorated with Au nanoparticles with a current density of ∼8.7 mA/cm 2 . Chu et al reported an IrO 2 /InGaN-NW photoanode with a current density of ∼10.9 mA/cm 2 and an applied-bias photon-to-current conversion efficiency (ABPE) of 3.5% .…”
Section: Introductionmentioning
confidence: 99%
“…17 Attempts to overcome the influence of the surface-trap states to improve the PEC-WS performance led to the passivation of the NW surface using noble metals, such as Au and IrO 2 . 18,19 For example, Liu et al reported an InGaN-nanorod photoanode decorated with Au nanoparticles with a current density of ∼8.7 mA/cm 2 . 18 Chu et al reported an IrO 2 /InGaN-NW photoanode with a current density of ∼10.9 mA/cm 2 and an applied-bias photon-to-current conversion efficiency (ABPE) of 3.5%.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Jiang et al found that the maximum solar-to-hydrogen efficiency is 4.3% for Cu-doped TiO 2 –12CdS NWs photoanode. Recently, Wang et al studied the PEC water splitting enhancement by Au@Pt-modified ZnO-CdS heterojunctions with a photocurrent density as high as 4.23 mA/cm 2 at 1.23 V. However, the influence of plasmonic metal nanoparticles on InGaN-based heterojunction semiconductors for the PEC water splitting was seldom reported. …”
Section: Introductionmentioning
confidence: 99%